The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1370/afm.2108
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Disparities of Ohioans With Developmental Disabilities Across the Lifespan

Abstract: We explored health care differences across the lifespan comparing people with developmental disabilities to people without developmental disabilities. Health care disparities are inequities occurring during the provision of and in access to health care that are experienced by socially disadvantaged populations. We discovered significant disparities between persons with and without developmental disabilities in health status, quality, utilization, access, and unmet health care needs. Our results highlight the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 7 publications
(6 reference statements)
0
13
0
1
Order By: Relevance
“…As an indicator of household income, we measured the proportion of women receiving support from the Special Supplemental Nutrition Program for Women, Infants and Children (WIC), which has income eligibility below 200% of the Federal Poverty level. 25,26…”
Section: Methodsmentioning
confidence: 99%
“…As an indicator of household income, we measured the proportion of women receiving support from the Special Supplemental Nutrition Program for Women, Infants and Children (WIC), which has income eligibility below 200% of the Federal Poverty level. 25,26…”
Section: Methodsmentioning
confidence: 99%
“…DD is defined as a severe, chronic state of health that affects cognitive and/or physical abilities, is diagnosed before age 22, results in an inability to manage at least three major activities of daily living (i.e., dressing, bathing, feeding, grooming), and causes dependency on aid for the duration of life. 9 The health care transition process is designed to educate young people with DD so they can reach an understanding in what skills will be necessary for them to take care of their own health care needs. To make this transition favorable depends on procuring suitable adult primary and specialty care.…”
Section: Limited Medical Home Accessmentioning
confidence: 99%
“…Cheak-Zamora and Thullen 4 report a serious shortage in health care providers who are educated and comfortable in managing services for CSHCN. A study by Prokup et al 9 found 81% of medical students surveyed answered they have no training for providing health care services for patients with disabilities. In addition, 58% of medical schools report adding a course of study focused on caring for patients with disabilities is not a primary concern.…”
Section: Limited Medical Home Accessmentioning
confidence: 99%
“…Additionally, in the intellectual disabilities population, substantial additional unmet health needs are found (Osugo, Morrison, Allan, Kinnear, & Cooper, ) when compared to the general population and people with intellectual disabilities are hospitalized more often for conditions that should be treatable in primary care (Balogh, Brownell, Ouellette‐Kuntz, & Colantonio, ; Balogh, Lake, Lin, Wilton, & Lunsky, ; Dunn, Hughes‐McCormack, & Cooper, ). As primary care appears to be particularly important for this vulnerable population, concerns are raised about the accessibility and quality of healthcare, including out‐of‐hours primary care (Carey et al., ; Cooper et al., ; Emerson, Hatton, Baines, & Robertson, ; Hosking et al., ; Perry et al., ; Prokup, Andridge, Havercamp, & Yang, ). Literature addressing healthcare for people with intellectual disabilities indicates that either the care for this patient group is approached as largely similar to the general population or as care that is highly specialized and very different from the general population (Balogh et al., ).…”
Section: Introductionmentioning
confidence: 99%